Syndromic anorectal malformation associated with Holt–Oram syndrome, microcephaly, and bilateral corneal opacity: a case report. (December 2016) - Usang, Usang; Agan, Thomas; Inyang, Akan; Emehute, John-Daniel; Itam, Itam
Abstract Background The occurrence of an anorectal malformation with Holt–Oram syndrome, microcephaly, and bilateral corneal opacity is rare and to the best of our knowledge has not previously been reported in the literature. Hence, there is a need to document our experience in this case and learn as much as possible from it. Case presentation We present the case of a Nigerian female neonate with a postnatal diagnosis of syndromic anorectal malformation associated with Holt–Oram syndrome, microcephaly, and bilateral corneal opacity. The infant had successful staged correction of her anorectal malformation but developed a metastatic Wilms' tumor and died before other corrective procedures could be instituted. Conclusions An anorectal malformation is here reported to occur with Holt–Oram syndrome, an association that has not been reported previously. To enhance the prognosis and quality of life of children with syndromic anorectal malformation, prenatal ultrasound monitoring of high-risk pregnancies and expertise in prenatal detection of congenital anomalies are invaluable in antenatal care.